Improving Learning Social Studies Outcomes through Flipped Classroom Model - Khilda Muminat, Ade; Tetep (Institut Pendidikan Indonesia, 2022)
Social Science lessons are still categorized as subjects with the lowest scores at every school level. This is caused by various things such as students who are less active and the selection of learning models by teachers who are still less effective. Therefore, there is a need for new innovations in the learning process in the classroom on social studies subjects in particular. One of the learning models that are considered capable of improving social studies learning outcomes is the Flipped Classroom learning model. The application of the Flipped Classroom learning model aims to determine the improvement of social studies learning outcomes and to determine students' perceptions of the application of the Flipped Classroom learning model. This study uses a quantitative approach with a quasi-experimental method with pre-test and post-test designs. The population is all students of class VIII MTs. Sirojul Huda Sukawening and his sample consisted of two classes, namely class VIII-A the control class and VIII-B as the experimental class. The instruments used in this study were test question sheets, observation sheets, and questionnaires. Based on the results of statistical analysis, the initial abilities of the two groups resulted in the same abilities. The result of the study can be concluded that there is a significant improvement in learning with the application of the Flipped Classroom learning model. The perception of experimental class students on the application of the Flipped Classroom learning model is also very good. Therefore, the application of the Flipped Classroom learning model can be used as an alternative for everyday learning, especially social studies subjects.